2017
DOI: 10.15789/1563-0625-2017-2-191-196
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Surface Il-6 Receptor Expression of Distinct Immune Cells in Progression of Chronic Obstructive Pulmonary Disease

Abstract: Адрес для переписки:Сидлецкая Каролина Андреевна Владивостокский филиал ФГБНУ «Дальневосточный научный центр физиологии и патологии дыхания» -Научно-исследовательский институт медицинской климатологии и восстановительного лечения 690105, Россия, г. Владивосток, ул. Русская, 73г. Тел.: 8 (423) 278-82-01; 278-82-02. Е-mail: d-karolina-a@mail Climatology and Rehabilitation, Vladivostok Branch 690105, Russian Federation, Vladivostok, Russkaya str., Медицинская иммунология, 2017. Т. 19, № 2. С. 191-196. do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
2
0
3
Order By: Relevance
“…In our earlier studies, it has been shown that IL-6R expression on the surface of circulating Th cells increases at last stages of COPD [21], thus indicating the importance of the activation of classical IL-6 signaling in these cells for the inflammatory process development during disease. In this study, we have found that severe COPD development accompanied by the formation of Th17associated cytokine profile is characterized by increase in the IL-6 blood levels and the number of Th cells expressing IL-6R.…”
Section: Discussionmentioning
confidence: 86%
“…In our earlier studies, it has been shown that IL-6R expression on the surface of circulating Th cells increases at last stages of COPD [21], thus indicating the importance of the activation of classical IL-6 signaling in these cells for the inflammatory process development during disease. In this study, we have found that severe COPD development accompanied by the formation of Th17associated cytokine profile is characterized by increase in the IL-6 blood levels and the number of Th cells expressing IL-6R.…”
Section: Discussionmentioning
confidence: 86%
“…В наибольшей степени экспрессия IL-6R возрастает на гранулоцитах (нейтрофилах) и Th-клетках, делая их мишенями для воздействия IL-6 посредством классического сигналинга. Основываясь на результатах исследований последних лет [29, 38,43], мы предполагаем, что классический путь передачи IL-6 сигнала может являться компенсаторным механизмом, направленным на подавление системной воспалительной реакции при ХОБЛ [4,5,7]. В связи с тем, что на всех стадиях ХОБЛ наблюдалась повышенная экспрессия IL-6R на Th-клетках, авторы оценили влияние IL-6 на формирование Т-хелперного иммунного ответа у пациентов с данной патологией.…”
Section: The Review Presents the Known Pathophysiological Mechanisms unclassified
“…В последние годы значительный интерес вызывает роль IL-6 в прогрессировании ХОБЛ. Согласно проведенным исследованиям, повышенный системный уровень IL-6 является отличительной чертой ХОБЛ и коррелирует со степенью воспаления нижних дыхательных путей и снижением легочной функции [2,14]. В связи с этим изучение молекулярных механизмов действия IL-6 при ХОБЛ вызывает большой интерес.…”
Section: иммунологические особенности хоблunclassified
“…диагностированы максимальные значения провоспалительных цитокинов IL-17, IL-21 и противовоспалительных -IL-10, TGF-β1, что указывает на продуцирующую активацию Th17-лимфоцитов, играющих роль дирижера воспалительной реакции. У 50% пациентов ( [2,11]. Кроме того, IL-6 способен подавлять апоптоз клеток посредством индукции антиапоптотических регуляторов.…”
Section: результаты и обсуждениеunclassified